2017
DOI: 10.21037/jtd.2017.02.88
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effects of preoperative obstructive pneumonitis or atelectasis and comparison with tumor size in non-small cell lung cancer

Abstract: Background: In the eighth TNM staging system proposal, lung cancer with part or complete obstructive pneumonitis/atelectasis was classified to T2 category, and dividing lines of T category were changed. We conducted this study to search prognostic effect of preoperative obstructive pneumonitis/atelectasis and its comparison with tumor size. Methods: We collected clinical characteristics, preoperative hematological indicators, follow-up information of 1,313 lung cancer patients. Chi-square test was used to sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…We also demonstrated that the presence of atelectasis could significantly affect OS (HR 2.047, 95 % CI 1.029− 4.071, P = 0.041), which is the same conclusion as the Pang study [30], in which 1177 preoperative patients were divided into subgroups by atelectasis and tumour size; in patients within the same tumour size subgroup, the OS was significantly shorter when atelectasis was absent (P = 0.033). However, for PFS, the results were not significant, suggesting the need for a larger sample size.…”
Section: Discussionsupporting
confidence: 84%
“…We also demonstrated that the presence of atelectasis could significantly affect OS (HR 2.047, 95 % CI 1.029− 4.071, P = 0.041), which is the same conclusion as the Pang study [30], in which 1177 preoperative patients were divided into subgroups by atelectasis and tumour size; in patients within the same tumour size subgroup, the OS was significantly shorter when atelectasis was absent (P = 0.033). However, for PFS, the results were not significant, suggesting the need for a larger sample size.…”
Section: Discussionsupporting
confidence: 84%
“…Since immunotherapy is a systematic treatment modality, changes indicating response are not limited to one location but can occur all over the body. This is particularly relevant in patients treated with anti PD-1 blockade where lymphadenopathy ( 14 , 15 ), parenchymal inflammations, edema ( 16 , 17 ), and compression atelectasis ( 18 ), can be observed. Ideally, during image response evaluation these conditions, together with tumor growth, should be monitored and quantified as they might hold valuable prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor size, given as the maximum diameter of the tumor, was one of independent prognostic factors of many solid tumors [1][2][3][4][5] . As for gastrointestinal carcinoma, several studies [6][7][8][9] a rmed that tumor size positively correlated with important prognostic factors and negatively impacted survival.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size has been veri ed to be associated with overall survival (OS) in many types of malignancy, and it is regarded as "T" stage of many solid tumors including breast, lung and liver cancers in the tumor-nodemetastasis (TNM) staging system of the Union for International Cancer Control (UICC) [1][2][3][4][5] . Despite the value of tumor size as a prognostic indicator in those solid tumors, the prognostic signi cance of tumor size in gastrointestinal tumors has not been widely realized.…”
Section: Introductionmentioning
confidence: 99%